Development of a digital LKPD on relations and functions to enhance mathematical conceptual understanding - Atika Suri; Mardiah Syofiana; Kashardi (LINEAR: Journal of Mathematics Education, 2026)
Conceptual understanding can be achieved through digital teaching materials, which can make teaching and learning activities more efficient and imaginative. Therefore, this study aims to develop a digital LKPD on relations and functions to enhance students' mathematical conceptual understanding and to determine its validity and practicality. This research is a Research and Development (R&D) study using the ADDIE development model. The study's subjects were students in class VIII C at SMPN 1 Kabawetan. The research instruments consisted of validation sheets, assessed by material and media experts, and student response questionnaires. The results showed that the developed digital LKPD received a valid category from material experts (average score of 0,75) and a highly valid category from media experts (average score of 0,81). Meanwhile, a limited trial produced an average result of 80%, indicating a practical category. Thus, the developed digital LKPD is feasible and practical for use in school mathematics instruction.